Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The relationship between international financing and domestic investment efficiency in Financing Development in the State of PalestineMr. Mahmoud Gawdat Mahmoud Qabaha, Dr. Abdul-Rahim Salim Shobaki2. The Impact of Management by wandering Around on the Perception of Organizational Justice  from the Perspective of Employees in the Directorates of the Jordanian Ministry of EducationMr. Ahmad Abdallah Obeidat, Dr. Riad Ahmad Aba Zaid3. The effectiveness of the human resources management strategy in improving employee performance by applying it to Meera Company in Asir RegionMrs. Maha Mushabab Ali Al-Qahtani, Mrs. Ebtisam Mohammed Khalid Fara, Mrs. Wejdan Mana Saeed Al- Qahtani, Dr. Abdullah Mahmoud Mohamed Badr4. Disciplinary Responsibility of the Government Employee in the Law of Saudi ArabiaDr. Hashem Baker Alshaikh5. Cloud Computing and The Future of Higher Education InstitutionsMr. Bekkari Mokhtar6. The role of transformational leadership in improving the performance of the Hajj and Umrah systemMr. Mohammad Saad Al-Ghalbi
Keywords: Journal of Economic, Administrative and Legal Sciences